Physical characterization of effective microorganism (em) paint on anti-corrosion - Rahim, Norin Hafizah; Onn, Munirah; Rahim, Nor Hidayah; Sabri, Nurul Hazwani; Hambali, Norhafini (2023)
This study focused on the physical characterization of effective microorganisms (EM) in acrylic emulsion paint. Cracking, flaking, and blistering are the common natural phenomena of coating failure. Five types of EM acrylic emulsion paint samples at different percentages of EM paint loading, which were 0%, 2%, 4%, 6%, and 8%, were used for this study. These formulations were mixed using a flocculation tester at a speed of 300 rpm for 10 minutes to ensure the mixture would disperse well. The performance of each EM paint loading will be evaluated in terms of water absorption, stability, soaking, and adhesion strength. This study revealed that 2% of EM paint is the best result. The water absorption test showed that the least percentage of water was absorbed at 2.73 %, while the 0% area was removed in the adhesion test. The stability test showed no changes in increasing the percentage of EM. In the soaking test, 2% of EM paint in HCl solution showed good corrosion coating compared to other EM paint loading. Lastly, images from SEM indicated that the rough surfaces of 2 % and 4 % of EM paint were indeed the ideal hardness properties.